Human Resource Development Strategy on Performance Through Job Crafting as an Intervening Variable - Annashihah, Hafshah (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2024)
This study aims to explore the impact of human resource development on performance through job crafting in the environment of Pesantren Tahfidz Maskanul Huffadz. The phenomenon of declining work quality, employee collaboration, and employee loyalty from 2019 to 2022 is suspected to occur due to the increasing number of students and pesantren administrators each year. This study uses an associative method to determine the relationship between the variables Education (X1), Training (X2), Career Development (X3), Job Crafting (Y), and Performance (Z), using path analysis and the PLS-SEM approach. The results show that the variables Education and Training have a positive and significant effect on Job Crafting, with t-statistic results of 2.294 and 4.556, respectively. Additionally, Job Crafting also has a positive and significant influence on employee performance, with hypothesis testing results showing a t-statistic of 5.313. However, other variables mediated or through job crafting do not show a significant influence. Based on these results, it can be concluded that Job Crafting has a direct impact on employee performance compared to research results calculated indirectly. The decline in employee performance is also suspected to be influenced by suboptimal education, training, and career development. Therefore, to improve employee performance at Pesantren Tahfidz Maskanul Huffadz, it is necessary to enhance the aspects of education and training as well as the implementation of more effective job crafting strategies.